PROPOSAL FOR THE DEVELOPMENT OF AN AGROECOLOGICAL-ECOEDUCATIONAL MODEL FOR THE MANAGEMENT OF PEST INSECTS IN AN AGRICULTURAL SETTLEMENT - Edison Pascal; Ernesto San-Blas; Helimar Vásquez; Mercedes Carrasquero Huerta (REDIELUZ, 2024)
The preservation of the environment requires considering through a participatory social practice the involvement of all the actors who directly and indirectly contribute to the development of community collective actions on the environment and agricultural management. The research work is subscribed in the educational field considering the fundamentals of eco-education and agroecology, through an approach focused on the qualitative paradigm. The methodological design that included this work was the constructivist investigation, whose guidelines were from Latorre. The proposed actions were consolidated with two eco-educational workshops, visits to the community, interviews and with the participation of all the actors involved. In this investigation, observation was fundamental, since the pest insects and the existing socio-environmental conditions were studied, and it was compared with interviews carried out with the residents. It is necessary to highlight that the eco-educational program was a fundamental tool for the agroecological management of pest insects and for the elaboration of a proposal for an eco-educational-agroecological model based on the community, and its socio-environmental and agricultural needs